Analysis of Determinants in Motor Vehicle Tax Revenue: An Empirical Study at the West Jakarta SAMSAT Office - Yusuf Yusrika (CV. Era Digital Nusantara, 2025)
This study aims to analyze the influence of the number of motor vehicles on the realization of Motor Vehicle Tax (PKB) revenue at the West Jakarta SAMSAT Office. Employing a quantitative associative approach, the research focused on the Motor Vehicle Tax Collection Service Unit (UPPPKB) using a saturated sampling method over the 2013-2022 reporting period (n=10). Secondary data collected through time-series observations were strengthened by primary data gathered via in-depth interviews to confirm field phenomena. The simple linear regression analysis reveals an anomalous finding where the number of motor vehicles has a significant negative influence on PKB revenue, with a significance value of 0.008 (< 0.05) and a t-statistic of -3.498. Despite a coefficient of determination (R2) of 60.5%, the growth in vehicle volume was counterintuitively followed by a surge in non-compliant vehicles, reaching 1.34 million units by 2022. These findings suggest that the growth of the tax base is no longer the primary driver of revenue due to high levels of non-compliance and tax avoidance behavior. Consequently, relevant authorities must strengthen active collection strategies and fiscal education to optimize the potential revenue loss.